OP22 Hand Hygiene and absenteeism in primary schools; a Cluster Randomised Controlled Trial. (2nd September 2014) - Nicholson, AL; Campbell, RM; Brookes, ST; Costelloe, CE; Chittleborough, CR; Bell, S; Noble, S; Young, E
Abstract : Background: Improved hand hygiene has the potential to reduce absenteeism in schools. The former Health Protection Agency, now part of Public Health England, developed a low cost educational intervention (Hands up for Max!) to promote hand washing in primary schools. The effectiveness of this intervention in reducing absenteeism was assessed in a cluster randomised controlled trial. Methods: One hundred and seventy eight primary schools in the South West of England were recruited and randomly allocated to intervention (n = 88) and control (n = 90) trial arms. Intervention schools received the 'Hands up for Max!' resource in the autumn term 2009 and control schools continued with their usual approach to hand washing. The primary outcome measures were pupil and staff absence data routinely collected and published by the Department of Education. Effects of the intervention on absence at school level were investigated using multi-level models. A detailed process evaluation was also embedded within the trial to look at intervention implementation, hand washing facilities, and pupil and staff hand hygiene knowledge and attitudes. Results: Intervention and control groups were comparable at baseline in terms of pupil numbers, age, gender, rate of absenteeism, socio-economic status, and ethnicity. At follow-up, pupil absence rates were similar between intervention and control groups; approximately 4.2 and 4.3 half days of absence per 100 days respectively. At follow-up the mean number of days of teacher absence per school year were also similar between intervention (3.13) and control (3.36) groups. Primary analyses were completed on an intention to treat basis. Multi-level models adjusting for baseline characteristics demonstrated minimal differences in pupil and teacher absence; a reduction of 0.05 half days per 100 days of pupil absence in the intervention group compared to control (95% CI -0.31 to 0.21, p = 0.695), and a reduction of 0.18 days of teacher absence in the intervention group compared to control (95% CI -1.28 to 0.91, p = 0.745). Conclusion: The Hands Up For Max! intervention did not alter pupil or teacher absence rates in this study. Structural factors, including being provided with the time, opportunity, and accessible, high quality facilities, are also likely to influence whether or not hand washing becomes routine. Such findings may be useful in explaining the lack of difference in absenteeism between trial arms.